The opportunity costs of environmental exclusion zones for renewable energy deployment - Paul Lehmann; Philip Tafarte (Helmholtz-Zentrum für Umweltforschung (UFZ), 2023)
Exclusion zones, like protected areas or setback distances, are the most common policy instrument to mitigate environmental impacts of human land-use, including the deployment of renewable energy sources. While exclusion zones may provide environmental benefits, they may also bring about opportunity costs. This paper aims to understand and quantify the drivers determining the opportunity costs related to environmental exclusion zones. Using a simple analytical model, we propose that opportunity costs of exclusion zones can be decomposed into a substitution effect (because production is shifted to sites with higher or lower marginal production costs) and an output effect (because more sites may be needed to satisfy demand for produced goods). We provide a numerical illustration for the opportunity costs for two examples of environmental exclusion zones - setback distances to settlements and forest bans - which are implemented for wind power deployment in Germany. The numerical illustration builds on a spatially explicit optimization model using GIS data for more than 100,000 potential wind turbine sites in Germany. Our analysis reveals that opportunity costs may primarily arise in terms of higher local environmental impacts of wind power generation. Opportunity costs are mainly due to the output effect for setback distances, and the substitution effect for forest bans. We also show that the actual sign and size of opportunity costs depends a lot on the cost criteria under consideration as well as the type and stringency of the environmental exclusion zone. Our analysis emphasizes the importance to properly understand possible opportunity costs, and compare them carefully with possible benefits when implementing exclusion zones. Interestingly, our analysis also shows that very restrictive setback distances may not be recommendable at all: In our analysis they turn out to increase the total disamenity costs produced by wind power deployment - contrary to the policy objective pursued by this instrument. We believe that our analytical insights are also helpful when thinking about the impacts of environmental exclusion zones applied to other fields of environmental policy, such as urban development or agriculture.
urn:nbn:de:gbv:3:2-963183
Keywords: Q23; Q24; Q28; Q42; R14; R32; 330; forest; Germany; land use; land-use restriction; setback distances; spatial modelling; wind power